Paul Nash’s Geological Enigma - Anna Reid (British Art Studies, 2018)
This essay explores the attunement of Nash’s work to pioneering geophysical research in England, connections which have not yet been fully recognized. In a context of the early-to-mid twentieth century, when geophysicists read the startling radioactivity of the land and worked mathematical equations to put a vastly ancient and sensational new age on the rocks of the earth, Nash’s landscape works, fraught with mathematical problems, equations, stones and bones, resonated afresh, beyond the confines of the Modern. Through these interests, I argue, Nash channelled and revitalized a British tradition of engagement with the aesthetics of the geological.